Quantum correlations between a pair of Raman photons from a single atom under arbitrary excitation condition - Patnaik, A.K.; Agarwal, G.S.; Ooi, Chong Heng Raymond; Scully, M.O. (2005)
The quantum correlation between a pair of Stokes and anti-Stokes photons, involving a Raman emission process is calculated. All realistic radiative and nonradiative decays are included in the calculation and the photon correlation between the pair for arbitrarily strong excitation fields and detunings are calculated. The correlation function shows photon antibunching, and a damped sinusoidal behavior with respect to the time delay between the measurement of the two photons. The current system can also produce four photon entanglement.